(untitled) (International Journal of Islamic Business, 2019)
When a Muslim die, there are four main things should be settled upon his death: funeral expenses, debt settlement, wasiyyah and faraid. Upon settling funeral and debt of the dead, estate management is one of the obligations required to be carried out by the heir using faraid. Nevertheless, based on the recent statistics issued by Amanah Raya Berhad, there are more than RM60 billions worth of properties of the deads in Malaysia have been frozen from being distributed to the respective heirs. Unfortunately, 95% of the properties belong to Muslims. Among reasons of the undistributed properties are due to awareness of the heirs, cost of property claims and law restriction. If this situation continuously happens, there will be a waste of capital in economy. To avoid this problem, hibah (inter vivos) and wasiyyah were suggested to be used as tools to avoid problems in distributing the wealth and properties to the heirs. Hence, the purpose of this research is to investigate behaviour of Malaysian Muslims in managing their estate specifically on wasiyyah and further to determine the factors that influence Muslims to choose wasiyyah. This is an empirical study which employed Logit Model analysis of data collected from surveys to Muslims in Malaysia. This study managed to collect 406 questionnaires and based on the result, it shows that age, health, religiosity and advantages are significant in explaining the Muslim behaviour to choose wasiyyah. The results also imply that Muslim would less likely to choose wasiyyah as to their estate planning if they have more age, good health condition and high level of religiosity and may tend to use the other tools available in Islam.